Controlled Chemoenzymatic Synthesis of Heparan Sulfate Oligosaccharides. (30th March 2018) - Lu, Weigang; Zong, Chengli; Chopra, Pradeep; Pepi, Lauren E.; Xu, Yongmei; Amster, I. Jonathan; Liu, Jian; Boons, Geert‐Jan
Abstract: A chemoenzymatic approach has been developed for the preparation of diverse libraries of heparan sulfate (HS) oligosaccharides. It employs chemically synthesized oligosaccharides having a chemical entity at a GlcN residue, which in unanticipated manners influences the site of modification by NST, C5‐Epi/2‐OST and 6‐OST1 /6‐OST3, thus resulting in oligosaccharides differing in N / O ‐sulfation and epimerization pattern. The enzymatic transformations defined fine substrate requirements of NST, C5‐Epi, 2‐OST, and 6‐OST.